Biological activity, molecular docking, and ADME predictions of amphibine analogues of Ziziphus spina-christi towards SARS-CoV-2 Mpro - Taufik Muhammad Fakih; Dwi Syah Fitra Ramadhan; Fitrianti Darusman (Biogenesis: Jurnal Ilmiah Biologi, 2021)
The main protease of the SARS-CoV-2 virus, SARS-CoV-2 Mpro, can be discovered as a promising target to treat the COVID-19 pandemic. The peptide-based inhibitors may present better options than small molecules to inhibit SARS-CoV-2 Mpro. Ziziphus spina-christi species reported have a peptide-based of alkaloids group, i.e., amphibine whose analogues can be identified the potential as an inhibitor of SARS-CoV-2 Mpro. The compound structure was drawn and optimized using semi-empirical AM-1 method using Quantum ESPRESSO v.6.6, while the biological activity using PASS. Prediction server and molecular docking simulation using MGLTools 1.5.6 with AutoDock 4.2 were performed. Afterward, the ADME profiles were predicted using the SWISS-ADME server. PASS server was predicting amphibine B-F and H showed potency both as antiviral and as a protease inhibitor. The molecular docking simulation of amphibine analogues showed lower binding energy than the native ligand. The binding energy of the native ligand was −7.69 Kcal/mol compared to the lowest binding energy of amphibine analogues was −10.10 Kcal/mol (amphibine-F). The ADME prediction showed that amphibine-F has the best bioavailability as an oral drug, amphibine-B, C, and D have good bioavailability, and amphibian-E and H have poor bioavailability. Concluded, amphibine B-F and H of amphibine analogues showed potency as COVID-19 treatment targeting SARS-CoV-2 Mpro.